The Tragedy of Women in Power: La Araucana and Sixteenth-Century Neo-Senecan Theatre - Choi, Imogen; Valencia, Felipe (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2020)
In cantos 32 and 33 of the third and final part of La Araucana, the narrator digresses from the matter of the Arauco War to recount the story of Queen Dido of Carthage in the anti-Virgilian, historiographic tradition whereby she was a chaste and prudent monarch who sacrificed herself for the good of her people. Ercilla’s version of Dido dialogues with contemporary Neo-Senecan tragedy, particularly two plays on the same subject: Cristóbal de Virués’s Elisa Dido (c. 1585) and Gabriel Lobo Lasso de la Vega’s La honra de Dido restaurada (1587). All three texts explore the tragedy that inevitably befalls commonwealths when women sit on the throne. We study these texts in light of the connections between epic and tragedy in Spanish letters of the late sixteenth century, the history and ideas surrounding women on the throne in early modern Spain, and the episodes of Ercilla’s poem that flank the Dido one.